Comparative Analysis of Crack Resistance of Fiber Metal Laminates with HS2 Glass/T700 Carbon Layers for Various Stress Ratios - Song, X.; Li, Z.Y; Shen, Y.; Chen, Y.L.; Zhang, J.Z. (Проблемы прочности, 2016)
Because of good crack growth resistance owe to the fibers between the aluminum layers, fiber metal laminates (FML) offer significant improvements compared to currently applied materials for aircraft structures. The crack resistance of different reinforced fibers, glass fiber, and carbon fiber, under stress ratio R = -1, 0.1, and 0.5, respectively, are analyzed through test data. The results showed significant scatter in the positive stress ratio and obvious difference between two outer aluminum layers. So, the failure criterions of metal materials specified in the test standard are unsuitable for the FMLs fatigue test, and it is a problem to determine the failure criterion according to the engineering applications. This study is an experimental investigations with respect to the FMLs crack resistance and a qualitative conclusions have been drawn from the data analysis.